(a) ![[\frac{9}{2.6} - \frac{2.5^{2} }{2.5} ]^{2}](https://tex.z-dn.net/?f=%5B%5Cfrac%7B9%7D%7B2.6%7D%20%20-%20%5Cfrac%7B2.5%5E%7B2%7D%20%7D%7B2.5%7D%20%5D%5E%7B2%7D)
Answer:
![[\frac{9}{2.6} - \frac{2.5^{2} }{2.5} ]^{2}](https://tex.z-dn.net/?f=%5B%5Cfrac%7B9%7D%7B2.6%7D%20%20-%20%5Cfrac%7B2.5%5E%7B2%7D%20%7D%7B2.5%7D%20%5D%5E%7B2%7D)
= ![[\frac{9}{2.6} - \frac{2.5*2.5 }{2.5} ]^{2}](https://tex.z-dn.net/?f=%5B%5Cfrac%7B9%7D%7B2.6%7D%20%20-%20%5Cfrac%7B2.5%2A2.5%20%7D%7B2.5%7D%20%5D%5E%7B2%7D)
= ![[\frac{9}{2.6} - \frac{2.5}{1} ]^{2}](https://tex.z-dn.net/?f=%5B%5Cfrac%7B9%7D%7B2.6%7D%20%20-%20%5Cfrac%7B2.5%7D%7B1%7D%20%5D%5E%7B2%7D)
*canceling 2.5 in numerator and denominator*
![= [\frac{9-(2.5)(2.6)}{2.6} ]^2\\*Using L.C.M of 2.6 and 1 which comes out to be '2.6'= [\frac{9-(6.5)}{2.6} ]^2\\= [\frac{2.5}{2.6} ]^2\\*multiplying and dividing by '10'= [\frac{2.5*10}{2.6*10} ]^2\\= [\frac{25}{26} ]^2\\= \frac{25^2}{26^2}\\= \frac{625}{676}\\= 0.925](https://tex.z-dn.net/?f=%3D%20%5B%5Cfrac%7B9-%282.5%29%282.6%29%7D%7B2.6%7D%20%5D%5E2%5C%5C%3C%2Fp%3E%3Cp%3E%2AUsing%20L.C.M%20of%202.6%20and%201%20which%20comes%20out%20to%20be%20%272.6%27%3C%2Fp%3E%3Cp%3E%3D%20%5B%5Cfrac%7B9-%286.5%29%7D%7B2.6%7D%20%5D%5E2%5C%5C%3D%20%5B%5Cfrac%7B2.5%7D%7B2.6%7D%20%5D%5E2%5C%5C%3C%2Fp%3E%3Cp%3E%2Amultiplying%20and%20dividing%20by%20%2710%27%3C%2Fp%3E%3Cp%3E%3D%20%5B%5Cfrac%7B2.5%2A10%7D%7B2.6%2A10%7D%20%5D%5E2%5C%5C%3D%20%5B%5Cfrac%7B25%7D%7B26%7D%20%5D%5E2%5C%5C%3D%20%5Cfrac%7B25%5E2%7D%7B26%5E2%7D%5C%5C%3D%20%5Cfrac%7B625%7D%7B676%7D%5C%5C%3D%200.925)
Properties used:
Cancellation property of fractions
Least Common Multiplier(LCM)
The least or smallest common multiple of any two or more given natural numbers are termed as LCM. For example, LCM of 10, 15, and 20 is 60.
(b) ![[[\frac{3x^{a}y^{b}} {-3x^{a} y^{b} } ]^{3} ] ^{2}](https://tex.z-dn.net/?f=%20%5B%5B%5Cfrac%7B3x%5E%7Ba%7Dy%5E%7Bb%7D%7D%20%7B-3x%5E%7Ba%7D%20y%5E%7Bb%7D%20%7D%20%5D%5E%7B3%7D%20%20%20%20%5D%20%5E%7B2%7D%20)
Answer:
![[[\frac{3x^{a}y^{b}} {-3x^{a} y^{b} } ]^{3}] ^{2}\\](https://tex.z-dn.net/?f=%5B%5B%5Cfrac%7B3x%5E%7Ba%7Dy%5E%7Bb%7D%7D%20%7B-3x%5E%7Ba%7D%20y%5E%7Bb%7D%20%7D%20%5D%5E%7B3%7D%5D%20%5E%7B2%7D%5C%5C)
*using
*
*Again, using
*
![= \frac{3x^{2*3a}y^{2*3b}} {-3x^{2*3a} y^{2*3b} } \\= (-1)\frac{3x^{6a}y^{6b}} {3x^{6a} y^{6b} }\\[\tex]*taking -1 common, denominator and numerator are equal*[tex]= -(1)\frac{1}{1}\\= -1](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B3x%5E%7B2%2A3a%7Dy%5E%7B2%2A3b%7D%7D%20%7B-3x%5E%7B2%2A3a%7D%20y%5E%7B2%2A3b%7D%20%7D%20%20%5C%5C%3D%20%28-1%29%5Cfrac%7B3x%5E%7B6a%7Dy%5E%7B6b%7D%7D%20%7B3x%5E%7B6a%7D%20y%5E%7B6b%7D%20%7D%5C%5C%5B%5Ctex%5D%3C%2Fp%3E%3Cp%3E%2Ataking%20-1%20common%2C%20denominator%20and%20numerator%20are%20equal%2A%3C%2Fp%3E%3Cp%3E%5Btex%5D%3D%20-%281%29%5Cfrac%7B1%7D%7B1%7D%5C%5C%3D%20-1)
Property used: 'Power of a power'
We can raise a power to a power
(x^2)4=(x⋅x)⋅(x⋅x)⋅(x⋅x)⋅(x⋅x)=x^8
This is called the power of a power property and says that to find a power of a power you just have to multiply the exponents.
Answer:
(f+g)(x)= 2x²+2x-2
Step-by-step explanation:
-x²+6x-1+3x²-4x-1 can be found by combining like terms.
2x²+2x-2
Answer:
Part A)
The equation in the point-slope form is:
![y-11=\frac{4}{3}\left(x-\left(-2\right)\right)](https://tex.z-dn.net/?f=y-11%3D%5Cfrac%7B4%7D%7B3%7D%5Cleft%28x-%5Cleft%28-2%5Cright%29%5Cright%29)
Part B)
The graph of the equation is attached below.
Step-by-step explanation:
Part A)
Given
The point-slope form of the line equation is
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
Here, m is the slope and (x₁, y₁) is the point
substituting the values m = 4/3 and the point (-2, 11) in the point-slope form of the line equation
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
![y-11=\frac{4}{3}\left(x-\left(-2\right)\right)](https://tex.z-dn.net/?f=y-11%3D%5Cfrac%7B4%7D%7B3%7D%5Cleft%28x-%5Cleft%28-2%5Cright%29%5Cright%29)
Thus, the equation in the point-slope form is:
![y-11=\frac{4}{3}\left(x-\left(-2\right)\right)](https://tex.z-dn.net/?f=y-11%3D%5Cfrac%7B4%7D%7B3%7D%5Cleft%28x-%5Cleft%28-2%5Cright%29%5Cright%29)
Part B)
As we have determined the point-slope form which passes through the point (-2, 11) and has a slope m = 4/3
The graph of the equation is attached below.
Subtraction is the operation that you should is to solve this problem